Apigenin and its impact on gastrointestinal cancers. Issue 1 (29th November 2012) - Lefort, Émilie C.; Blay, Jonathan
<x xml:space="preserve">Abstract</x> Apigenin (4′, 5, 7‐trihydroxyflavone, 5, 7‐dihydroxy‐2‐(4‐hydroxyphenyl)‐4H‐1‐benzopyran‐4‐one) is a flavonoid found in many fruits, vegetables, and herbs, the most abundant sources being the leafy herb parsley and dried flowers of chamomile. Present in dietary sources as a glycoside, it is cleaved in the gastrointestinal lumen to be absorbed and distributed as apigenin itself. For this reason, the epithelium of the gastrointestinal tract is exposed to higher concentrations of apigenin than tissues at other locations. This would also be true for epithelial cancers of the gastrointestinal tract. We consider the evidence for actions of apigenin that might hinder the ability of gastrointestinal cancers to progress and spread. Apigenin has been shown to inhibit cell growth, sensitize cancer cells to elimination by apoptosis, and hinder the development of blood vessels to serve the growing tumor. It also has actions that alter the relationship of the cancer cells with their microenvironment. Apigenin is able to reduce cancer cell glucose uptake, inhibit remodeling of the extracellular matrix, inhibit cell adhesion molecules that participate in cancer progression, and oppose chemokine signaling pathways that direct the course of metastasis into other locations. As such, apigenin may provide some additional benefit beyond existing drugs in slowing the emergence of metastatic disease.